Managing Economic Crisis in Southeast Asia - Saw, Swee-Hock, 1931-2021 (Book collections on Project MUSE., 2011)
This book incorporates a selection of eight revised papers presented at the Conference on "Managing Economic Crisis in Southeast Asia", organized jointly by the Saw Centre for Financial Studies, NUS Business School and the Institute of Southeast Asian Studies, in January 2010. The chapters deal with the management of the 2008-09 economic crisis in Singapore, Malaysia, Thailand, Vietnam, the Philippines, Indonesia, and the region as a whole. They represent an analysis of the impact of the economic crisis and the stimulus packages that were swiftly put in place by the governments to mitigate the economic recession and to pave the way for a quick recovery. The success of the monetary and fiscal policy measures in engendering a strong economic recovery in these countries is also discussed in considerable depth. The book, with contributions from experts on the topics covered, will be extremely valuable to businessmen, analysts, academics, students, policy-makers and the general public interested in seeking a greater understanding of the sub-prime crisis that led to the global economic recession.